Allocation of glycerolipids and glycerophospholipids from adults to eggs in Daphnia magna: Perturbations by compounds that enhance lipid droplet accumulation. (November 2018) - Fuertes, Inmaculada; Jordão, Rita; Casas, Fina; Barata, Carlos
Abstract: Analysis of the disruptive effects of chemicals on lipids in invertebrates is limited by our poor knowledge of the lipid metabolic pathways and the complete lipidome. Recent studies shown that juvenoids and bisphenol A disrupted the dynamics of lipid droplets in the crustacean Daphnia magna . This study used ultra-high performance liquid chromatography/time-of-flight mass spectrometry (UHPLC/TOFMS) to study how juvenoids (pyriproxyfen and methyl farnesoate) and bisphenol A disrupt the dynamics of glycerophospholipids and glycerolipids in Daphnia adults and their allocation to eggs. Lipidomic analysis identified 234 individual lipids corresponding to three classes of glycerolipids, seven of glycerophospholipids, and one of sphingolipids, of which 194 changed according to the chemical treatments and time. Adult females in the control and bisphenol A treatment groups had low levels of triacylglycerols but high levels of glycerophospholipids, whereas those in the juvenoid treatment groups had high levels of triacylglycerols and low levels of glycerophospholipids. The opposite trend was observed for the lipid contents in the eggs produced. Because the juvenoids reduced reproduction dramatically, the females allocated less triacylglycerols to their eggs than the controls did. Interestingly, females exposed to bisphenol A allocated less triacylglycerols to their eggs despite producing a similar number of eggs as that of the controls. Thin-layer chromatography analyses confirmed the UHPLC/TOFMS results and allowed qualitative determination of cholesterol, which was also accumulated in females exposed to the juvenoids. Graphical abstract: Highlights: Whole lipidome of Daphnia magna females exposed to compounds that enhanced lipid droplet accumulation were studied. 194 out of 234 individual lipids analysed changed across treatments. Juvenoid compounds reduced egg production promoting the accumulation of triacylglycerols. Bisphenol A prevented the transfer of triacylglycerols to eggs, increasing their accumulation in reproductive females. Abstract : Bisphenol A and juvenoid compounds promoted the accumulation of triacylglycerols into lipid droplets in the crustacean D. magna and prevented their allocation to reproduction.